GIS Analysis of Land Cover Changes on the Territory of the Prokuplje Municipality - Aleksandar Valjarević; Dragica Živković; Dragana Valjarević; Vladica Stevanović; Jelena Golijanin (The Scientific World Journal)
The monitoring of the territory of Prokuplje Municipality was done based on 1 : 25,000 topographic maps in three different time periods (1969, 1974, and 1984) and land cover map in 2012. Analogous topographic maps done in 1969, 1974, and 1984 were used, while in 2012 the land cover map obtained by using CORINE-like approach was used. Topographic maps are developed by aerial campaign, and today they are replaced by satellite images. Topographic maps were scanned, and raster form was transformed to vector data with Geo Media Professional 6.1 and Global Mapper software. The monitoring in the period of 1969–2012, on the area of 758300000 m2, was performed, where some parameters were analyzed. In particular, the changes of natural resources, primarily forest lands, were observed as well as the type of land susceptible to primary erosion, including the level of urbanization and level of agricultural land. The obtained results clearly showed changes in forestation within the 43-year-long period, as well as changes in primary erosion and urbanization, while at the level of agricultural land, slight changes were found. The paper also involved transition of social factors from 1969 to 2012, expressed as a change between the earth and forest layer.